√√5+2 +√√5-2/√√5+1 please solve it
Answers
•●○ ANSWER ○●•
Given,
P = {√(√5 + 2) + √(√5 -2)}/√(√5 + 1) - {√3 - 2√2}
Now,
{√[√5 + 2]+√[√5–2]}
√[√5 + 1]
= {√[√5+2]+√[√5–2]}√[√5–1]
(√[√5 + 1] √[√5 – 1])
= {√[(√5+2)(√5–1)]+√[(√5–2)(√5–1)]}
√[(√5+1)(√5–1)]
= {√[5–√5+2√5–2]+√[5–√5–2√5 + 2] }
√[5 – 1]
= { √[3 + √5] + √[7 – 3√5] }
2
= { √[(6 + 2√5)/2] + √[(14 – 6√5)/2] }
2
= { √[(1 + 5 + 2√5)/2] + √[(9 + 5 – 6√5)/2] }
2
= { √[(1 + √5)2 /2] + √[(3 – √5)2 /2] }
2
= { (1 + √5)/√2 + (3 – √5)/√2 }
2
= { (1 + √5) + (3 – √5) }
(2√2)
= 4/(2√2)
= √2
Again,
√[3 – 2√2] = √[2 + 1 – 2√2]
= √[(√2 – 1)2 ]
= √2 – 1
Now,
P = { √[√5 + 2] +√[√5 – 2] }
√[√5 + 1] – √[3 – 2√2]
=> P = √2 – (√2 – 1)
=> P = √2 – √2 + 1
=> P = 1